The purpose of the woman’s covering and preservation and its impact on the rulings of Hajj (As a model) - Nour, Najla Mohammed Burhan Mohammed; Al-Moqbel, Nada Turki (Journal of Islamic Sciences, 2024)
This research aims to reveal the purpose of the woman’s covering and preservation and its impact on the rulings of Hajj. This is done through gathering the jurisprudential branches influenced by it and conducting a comparative jurisprudential study. This study will then conduct an analysis of the texts of jurists related to it in those branches for the purpose of clarifying the impact of this purpose. It will cast light on its extent and parameters and do affirming its objectives. The study begins by establishing the purpose of the woman’s covering and preservation then identifies and regulates its impact through the opinions of scholars regarding the branches and jurisprudential issues related to it in the rulings of Hajj. It has examined them in a comparative manner, discussing them, and weighing their merits. This analysis reveals through this diversity, their impacts on these rulings; it serves as independent evidence in many cases and also reflects the rationale behind the evidence, among other aspects that confirm its status as a legal purpose considered by Sharia in its rulings concerning women and their circumstances in general, as well as specifically in the rulings of Hajj related to them.